Nicotine Has a Therapeutic Window of Effectiveness in a Drosophila melanogaster Model of Parkinson’s Disease - Brady T. Mannett; Braden C. Capt; Krista Pearman; Lori M. Buhlman; John M. VandenBrooks; Gerald B. Call (Parkinson's Disease)
Strong epidemiological evidence and studies in models of Parkinson’s disease (PD) suggest that nicotine may be therapeutically beneficial in PD patients. However, a number of clinical trials utilizing nicotine in PD patients have had mixed results, indicating that either nicotine is not beneficial in PD patients, or an important aspect of nicotine therapy was absent. We hypothesized that nicotine must be administered early in the adult fly life in order to have beneficial effects. We show that continuous early nicotine administration improves both climbing and flight deficiencies present in homozygous park25 mutant PD model Drosophila melanogaster. Using a new climbing assay, we identify several climbing deficiencies in this PD model that are improved or rescued by continuous nicotine treatment. Amongst these benefits, it appears that nicotine improves the ability of the park25 flies to descend the climbing vial by being able to climb down more. In support of our hypothesis, we show that in order for nicotine benefits on climbing and flight to happen, nicotine administration must occur in a discrete time frame following adult fly eclosure: within one day for climbing or five days for flight. This therapeutic window of nicotine administration in this PD model fly may help to explain the lack of efficacy of nicotine in human clinical trials.